2014
DOI: 10.1002/anie.201410062
|View full text |Cite
|
Sign up to set email alerts
|

Integrated One‐Flow Synthesis of Heterocyclic Thioquinazolinones through Serial Microreactions with Two Organolithium Intermediates

Abstract: The synthesis of pharmaceutical compounds via short-lived intermediates in a microreactor is attractive, because of the fast flow and high throughput. Additionally, intermediates can be utilized sequentially to efficiently build up a library in a short time. Here we present an integrated microfluidic synthesis of biologically active thioquinazolinone libraries. Generation of o-lithiophenyl isothiocyanate and subsequent reaction with aryl isocyanate is optimized by controlling the residence time in the microrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Concerning laboratory experiments, many authors successfully synthesized a variety of organolithium compounds within microstructured devices, by taking advantage of precisely adjustable reaction conditions to easily control those highly exothermic and fast reactions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Key examples are studies by the groups of Yoshida, Feng, and Browne, as shown below.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning laboratory experiments, many authors successfully synthesized a variety of organolithium compounds within microstructured devices, by taking advantage of precisely adjustable reaction conditions to easily control those highly exothermic and fast reactions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Key examples are studies by the groups of Yoshida, Feng, and Browne, as shown below.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been reported for the synthesis of both 2‐thioxo‐2,3‐dihydroquinazolin‐4(1 H )‐ones and 2‐amino‐4 H ‐benzo[ d ][1,3]thiazin‐4‐ones . In general, these valuable frameworks are synthesized from anthranilic acid derivatives and isothiocyanates under harsh conditions.…”
Section: Methodsmentioning
confidence: 99%
“…For 2‐thioxo‐2,3‐dihydroquinazolin‐4(1 H )‐ones, low yields of around 50 % are often obtained. Recently, Tim and co‐workers reported a concise continuous‐flow integrated synthesis of S‐benzylic thioquinazolinone derivatives in overall excellent yields . Although several other methods have been developed, long synthetic routes, toxic reagents, or a lack of available substrates have limited them from wider application.…”
Section: Methodsmentioning
confidence: 99%
“…Various s ‐benzylic thioquinazolinone derivatives were synthesized within 10 s in high yields at room temperature. Also the interesting thing about this methodology is that three steps involved two organolithium intermediates, an isothiocyanate‐functionalized aryllithium intermediate, and a subsequent lithium thiolate intermediate were conducted by one‐flow and sequential operation (Figure ) …”
Section: Ultrafast Syntheses In Organic and Inorganic Chemistrymentioning
confidence: 99%